2015
DOI: 10.1007/s12613-015-1155-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel diffusion model considering curvature radius at the bonding interface in a titanium/steel explosive clad plate

Abstract: This article introduces an element diffusion behavior model for a titanium/steel explosive clad plate characterized by a typical curved interface during the heat-treatment process. A series of heat-treatment experiments were conducted in the temperature range from 750°C to 950°C, and the effects of heat-treatment parameters on the microstructural evolution and diffusion behavior were investigated by optical microscopy, scanning electron microscopy, X-ray diffraction analysis, and electron-probe microanalysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…As shown in Figure 6b,c, there was no obvious diffusion region of Ti and Fe at the straight bonding interface, while a mono-peak of carbon element was observed at the place where the black layer existed (Figure 6b). Therefore, the so-called black layer was actually the result of the segregation phenomena of carbon element, and Jiang et al [47] also observed this phenomenon in their study. The vortex shown in Figure 6a formed due to the liquid metal jet in the front of the detonation wave propagation was intercepted during the explosive welding [48,49], where multiple elements such as Ti, Fe, C, and Mn were mixed and dissolved to produce various hard and brittle intermetallic compounds including FeTi, Fe2Ti and TiC [50,51], and cracks were easy to be formed in the vortex during the rolling process.…”
Section: Microstructure Observation and Composition Analysismentioning
confidence: 78%
See 1 more Smart Citation
“…As shown in Figure 6b,c, there was no obvious diffusion region of Ti and Fe at the straight bonding interface, while a mono-peak of carbon element was observed at the place where the black layer existed (Figure 6b). Therefore, the so-called black layer was actually the result of the segregation phenomena of carbon element, and Jiang et al [47] also observed this phenomenon in their study. The vortex shown in Figure 6a formed due to the liquid metal jet in the front of the detonation wave propagation was intercepted during the explosive welding [48,49], where multiple elements such as Ti, Fe, C, and Mn were mixed and dissolved to produce various hard and brittle intermetallic compounds including FeTi, Fe2Ti and TiC [50,51], and cracks were easy to be formed in the vortex during the rolling process.…”
Section: Microstructure Observation and Composition Analysismentioning
confidence: 78%
“…As shown in Figure 6b,c, there was no obvious diffusion region of Ti and Fe at the straight bonding interface, while a mono-peak of carbon element was observed at the place where the black layer existed (Figure 6b). Therefore, the so-called black layer was actually the result of the segregation phenomena of carbon element, and Jiang et al [47] also observed this phenomenon in their study.…”
Section: Microstructure Observation and Composition Analysismentioning
confidence: 78%